Pemberdayaan UMKM Melalui Pembuatan Nomor Induk Berusaha (NIB) Sebagai Langkah Awal Legalitas Usaha - Azzahra, Afitra; Handayani, Wiwik (LPPM Politeknik Piksi Ganesha, 2024)
MSMEs are the backbone of economic growth in Indonesia. However, the greater the potential of MSMEs, the more challenges business actors must face, one of it is regarding business legality. One important step in obtaining business legality is to create a Business Identification Number (NIB). The reality is that there are many business actors who do not have a NIB due to many factors. BTPN Syariah invites students to participate in empowering MSMEs by providing regular assistance to their customer to strengthen their knowledge and skills in entrepreneurship. The methods used in this empowerment program are observation, interviews, material teaching, and practice. The results of this empowerment is assistance in making NIB. By creating an NIB, business actors are expected to be able to maximize the benefits to optimize the business they are running, such as getting ease in financing, wider market access, and ease in processing other licensing documents